2023
DOI: 10.3390/su151813441
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Paradigm Shift on Mapping Muddy Waters with Sentinel-2 Using Machine Learning

Christos Psychalas,
Konstantinos Vlachos,
Anastasia Moumtzidou
et al.

Abstract: The quality of drinking water is a critical factor for public health and the environment. Inland drinking water reservoirs are essential sources of freshwater supply for many communities around the world. However, these reservoirs are susceptible to various forms of contamination, including the presence of muddy water, which can pose significant challenges for water treatment facilities and lead to serious health risks for consumers. In addition, such reservoirs are also used for recreational purposes which su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…They found that bands 5, 6, 7, and 8A contributed the most to this end. In another study by Psychalas et al [105], their results showed significant contributions from bands 4, 5, 8A, 11, and 12 for identifying highly turbid waters in reservoirs. Specifically, the contributions from bands 11 and 12 were attributed to the variety of land classes and cloud formations present in their remote sensing data.…”
Section: Bands and Indices Selectionmentioning
confidence: 91%
“…They found that bands 5, 6, 7, and 8A contributed the most to this end. In another study by Psychalas et al [105], their results showed significant contributions from bands 4, 5, 8A, 11, and 12 for identifying highly turbid waters in reservoirs. Specifically, the contributions from bands 11 and 12 were attributed to the variety of land classes and cloud formations present in their remote sensing data.…”
Section: Bands and Indices Selectionmentioning
confidence: 91%